A Survey of Labor Epidural Practices at Obstetric Anesthesia Fellowship Programs in the United States. Issue 1 (22nd March 2023) - Callahan, E.; Yeh, P.; Carvalho, B.; George, R.B.
Abstract : ( Can J Anaesth . 2022;69:591–596) Methods of delivery for labor epidural analgesia (LEA) are varied and numerous, with areas of consensus and departure in the consideration of best practices among anesthesia providers. With variations in placement technique, choosing to use a combined spinal epidural (CSE) with the additional delivery of intrathecal (IT) medication, opting for an initial bolus delivery, and the multiplying variables of analgesic selection in the epidural or IT space, practice heterogeneity may become a norm that is worth reconsidering in favor of an evidence-based consensus. Contemporary LEA practices were surveyed in American Council for Graduate Medical Education (ACGME)-accredited obstetric anesthesiology fellowship training programs to estimate the current thought on optimal LEA care.